Is There a Rationale for Penile Rehabilitation Following Radical Prostatectomy?. (January 2015) - Barazani, Yagil; Stahl, Peter J.; Nagler, Harris M.; Stember, Doron S.
Erectile function recovery after radical prostatectomy (RP) is an increasingly prominent quality-of-life outcome following surgery. Following RP many men, despite the advent of cavernous nerve-sparing surgical technique, have moderately or significantly impaired erectile function (EF). The term penile rehabilitation (PR) is used to define interventions that maintain the health of erectile tissue in the context of nervous, vascular, and structural tissue injury. The goal of PR is to regain, as closely re-approximate, preoperative erectile function. PR is based on an increasing volume of preclinical and clinical data, but conclusive evidence of efficacy has not been established, and therefore the concept of PR remains controversial. The optimal PR regimen has not been established, but all strategies rely on one or more erectile dysfunction treatments to be administered on a regular basis regardless of actual use for sexual activity. This review highlights recent studies and evidence related to PR.